(untitled) (Studia Prawnicze / The Legal Studies, 1984)
The rules of procedure of the Diet binding since iMaiich 1, 1957 and many times amended show a permanent trend to go beyond the regulations on the work of the Chamber and to interfere with the sollutions which ’even have a constitutional character_ The rules of procedure considerably contributed to shaping the Diet on the basis of Polish parliamentary tradition. It sew that the fact that the rules of procedure of the Diet are treated without attaching great, importance to the fact of underestimating law and treating it instrumentally,- the manifestation of which is open, non-constitutional system of sources of law, comprising resolutions of various state authorities and, in particular, resolutions of the government. The result Of this phenomenon Lis :iTrlluiding into the rules of regulation’s cif the Diet various elements having no direct connection with the mode of work of the Diet. There is also no clear conception of practical solutions and no conception on the representative, which is manifested by outdated electoral system and replacing norms of higher rank by incomplete resolutions. The legislative work of the Diet which has been rapidly being developed for 3 years does not adequately deal with external relations of the Chamber itself, which should be regulated by the Constitution and law, while the rules procedure of the Diet should deal With internal work of the Chamber and its members.